Phosphotungstic acid as an efficient solid catalyst for intramolecular rearrangement of benzyl phenyl ether to 2-benzyl phenol - Bhure, Mahesh H.; Rode, Chandrashekhar V.; Chikate, Rajeev C.; Patwardhan, Neeraj; Patil, Shraddha (Catalysis Communications, 2007)
An heteropoly acid (phosphotungstic acid, PTA) was found to be a promising solid acid catalyst as an alternative to the conventional stoichiometric reagents for the rearrangement of benzyl phenyl ether giving 2-benzyl phenol as a major product and 4-benzyl phenol and dibenzylated phenols as side products. Catalyst was recovered from the reaction mixture and reused again without loss of activity. Based on the observed product distribution for various substrates a plausible catalytic reaction pathway has also been proposed. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: benzyl phenyl ether; Intramolecular rearrangement; Phosphotungstic acid

Solid acid catalysts: modification of acid sites and effect on activity and selectivity tuning in various reactions - Rode, C. V.; Garade, Ajit C.; Chikate, Rajeev C. (Catalysis Surveys from Asia, 2009)
The effects of acidity and variation in concentration of acid sites of dodecatungstophosphoric acid (DTP), supported DTP and montmorillonite-K catalysts were studied for various organic reactions such as the hydroxyalkylation of phenols to bisphenols, intramolecular rearrangement of benzyl phenyl ether (BPE) to 2-benzyl phenol (2-BP) and selective cleavage of tert-butyldimethylsilyl (TBDMS) ether into the corresponding alcohol. Both dodecatungstophosphoric acid (DTP) impregnated on silica (SiO(2)) and montmorillonite catalysts showed the highest catalyst activity with 90-95% selectivity to bisphenol for the hydroxyalkylation of phenols to give bisphenol. Temperature Programmed Desorption (TPD) of ammonia and activity results of various catalysts showed that an appropriate combination of both strong and weak acidic sites in the catalyst was highly desirable for high bisphenol selectivity. A 10% DTP/SiO(2) catalyst was found to be highly selective for the cleavage of TBDMS ether into the corresponding alcohol at room temperature giving a high TON of 9.5 x 10(5) even after the 4th recycle. DTP was also found to be a promising solid acid catalyst for the intramolecular rearrangement of BPE giving 2-BP.
Keywords: Acidity tuning; Catalytic cleavage; Hydroxyalkylation; Intramolecular rearrangement; solid acid catalysts